Relationship of self-reported body size and shape with risk for prostate cancer: A UK case-control study - Mohammad Aladwani; Artitaya Lophatananon; Fredie Robinson; Aneela Rahman; William Ollier; Zsofia Kote-Jarai; David Dearnaley; Govindasami Koveela; Nafisa Hussain; Reshma Rageevakumar; Diana Keating; Andrea Osborne; et al. (2020)
Introduction Previous evidence has suggested a relationship between male self-reported body size and the risk of developing prostate cancer. In this UK-wide case-control study, we have explored the possible association of prostate cancer risk with male self-reported body size. We also investigated body shape as a surrogate marker for fat deposition around the body. As obesity and excessive adiposity have been linked with increased risk for developing a number of different cancers, further investigation of self-reported body size and shape and their potential relationship with prostate cancer was considered to be appropriate. Objective The study objective was to investigate whether underlying associations exist between prostate cancer risk and male self-reported body size and shape. Methods Data were collected from a large case-control study of men (1928 cases and 2043 controls) using self-administered questionnaires. Data from self-reported pictograms of perceived body size relating to three decades of life (20’s, 30’s and 40’s) were recorded and analysed, including the pattern of change. The associations of self-identified body shape with prostate cancer risk were also explored.